Pengaruh Budaya Organisasi terhadap Kinerja Karyawan - Agustina, Dini Rahma; Andriani, Andriani; Mahfudhotin, Mahfudhotin (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2025)
Organizational culture is a system of values and norms that have taken effect, followed and agreed upon by each member as a guide in behaving and solving problems in their organization. Organizational culture is closely related to employee performance because the organizational culture in a company is able to foster the work spirit of the people in it. This study aims to determine the organizational culture and employee performance according to employees in the production department of PT Sukses Mitra Sejahtera, Krandang Village, Kras District, Kediri Regency. The method used is a quantitative method. Variables X and Y are in the